2014
DOI: 10.1249/mss.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses to Diesel Exhaust Exposure Are Modified by Cycling Intensity

Abstract: Respiratory and metabolic responses to low-intensity, but not high-intensity, cycling in DE exceed FA. Practically, the greater responses during low-intensity exercise in DE could have implications for individuals with cardiopulmonary disease. Also, the elevated RPE during DE could impair performance in self-paced exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 32 publications
1
49
1
1
Order By: Relevance
“…There is some evidence for a feedback loop between ventilation and air pollution inhaled dose, in such that air pollution exposure may marginally augment or attenuate ventilation 45 , but it is not expected that this interaction will affect daily inhaled doses significantly, except in very highly polluted environments and in very active people 46 .…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for a feedback loop between ventilation and air pollution inhaled dose, in such that air pollution exposure may marginally augment or attenuate ventilation 45 , but it is not expected that this interaction will affect daily inhaled doses significantly, except in very highly polluted environments and in very active people 46 .…”
Section: Discussionmentioning
confidence: 99%
“…They reviewed elite endurance (aerobic) athletes and mixed-sports (aerobic and anaerobic) athletes and found that they survive longer than the general population, as indicated by lower mortality and higher longevity. For example, a former career elite athlete would be protected from both type 2 diabetes and impaired glucose tolerance in later life [49] and an athlete doing high-but not low-intensity cycling may resist diesel exhaust exposure [50].…”
Section: External Activitiesmentioning
confidence: 99%
“…The higher the ASH fitness is, the stronger the resistance of the ASH is. For example, an athlete doing high-but not low-intensity cycling may resist diesel exhaust exposure [50]. Therefore, a global PBM on an organism may promote the normalization of a dysfunctional action in a dPBM way or upgrade the normal action in an iPBM way and then modulate organism health, suboptimal health, and disease.…”
Section: Action-dependent Organism Photobiomodulationmentioning
confidence: 99%
“…Therefore, although physical activity is strongly recommended for all its wellknown health benefits, its effects when practiced in polluted environments are questionable [3,5,8,16]. For instance, although Jacobs et al (2010) demonstrated that acute cycling in an air-polluted area results in impaired systemic inflammatory response, Giles et al (2014) demonstrated that different exercise intensities can result in different responses when practiced in polluted areas [3,5]. On the other hand, a mouse experimental study showed that chronic exercise during diesel exhaust particle (DEP) exposure significantly inhibits the DEP-induced inflammatory response [16].…”
Section: Introductionmentioning
confidence: 99%